Quality of Life Profile, Overweight-Obesity and Sedentary Behavior in Elementary and High School Children of Guanacaste - Pedro Ureña-Bonilla; Felipe Araya-Ramírez; Braulio Sánchez-Ureña; Jorge Salas-Cabrera; Luis Alberto Blanco-Romero (Universidad Nacional, Costa Rica, 2010)
The purpose of this study was to identify the quality of life profile, overweight-obesity and sedentary behavior in a group of elementary and high school children of Guanacaste. 635 students participated in the study. The participants completed a protocol by which they were anthropometrically evaluated, and also filled up a questionnaire related to sedentary behavior and quality of life. In general, the findings reflected a prevalence of overweight and obesity of 13, 9%. The most important sedentary activities were, in descending order, the small screen (watching TV, video games, computer), and certain social and cultural activities. The self-reported quality of life index was within acceptable limits but not exceeding 80 points on a scale of 1-100. There was no significant relationship between the rate of the overall quality of life, overweight, obesity and some sedentary behaviors, although some anthropometric parameters like percentage of body fat and body weight showed significant correlation with sedentary behavior and specific aspects belonging to quality of life. The study provides valuable information to health authorities, directors of educational institutions and parents about key issues related to child development.